Comparison between external locking plate fixation and conventional external fixation for extraarticular proximal tibial fractures: a finite element analysis - Dejan Blažević; Janoš Kodvanj; Petra Adamović; Dinko Vidović; Zlatko Trobonjača; Srećko Sabalić (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background Good clinical outcomes for locking plates as an external fixator to treat tibial fractures have been reported. However, external locking plate fixation is still generally rarely performed. This study aimed to compare the stability of an external locking plate fixator with that of a conventional external fixator for extraarticular proximal tibial fractures using finite element analysis. Methods Three models were constructed: (1) external locking plate fixation of proximal tibial fracture with lateral proximal tibial locking plate and 5-mm screws (ELP), (2) conventional external fixation of proximal tibial fracture with an 11-mm rod and 5-mm Schanz screws (EF-11), and (3) conventional external fixation of a proximal tibial fracture with a 7-mm rod and 5-mm Schanz screws (EF-7). The stress distribution, displacement at the fracture gap, and stiffness of the three finite element models at 30-, 40-, 50-, and 60-mm plate–rod offsets from the lateral surface of the lateral condyle of the tibia were determined. Results The conventional external fixator showed higher stiffness than the external locking plate fixator. In all models, the stiffness decreased as the distance of the plate–rod from the bone surface increased. The maximum stiffness was 121.06 N/mm in the EF-11 model with 30-mm tibia–rod offset. In the EF-7 model group, the maximum stiffness was 40.00 N/mm in the model with 30-mm tibia–rod offset. In the ELP model group, the maximum stiffness was 35.79 N/mm in the model with 30-mm tibia–plate offset. Conclusions Finite element analysis indicated that external locking plate fixation is more flexible than conventional external fixation and can influence secondary bone healing. External locking plate fixation requires the placement of the plate as close as possible to the skin, which allows for a low-profile design because the increased distance from the plate to the bone can be too flexible for bone healing. Further experimental mechanical model tests are necessary to validate these finite element models, and further biological analysis is necessary to evaluate the effect of external locking plate fixation on fracture healing.